Relationship between serum ferritin and growth status of pediatric transfusion dependent thalassemia - Andi Cahyadi; I Dewa Gede Ugrasena; Mia Ratwita Andarsini; Maria Christina Shanty Larasati; Raden Muhammad Zulfan Jauhari; Diah Kusuma Arumsari (Babol University of Medical Sciences, 2023)
Background: Growth retardation is a long-term complication in pediatric transfusion-dependent thalassemias (TDTs), presented as short-stature and upper body segment shortening. The cause of this condition was chronic hypoxia, iron overload, endocrinopathy, inadequate transfusion, and iron chelation. We analyze the relationship between ferritin level and growth status of pediatric TDTs. Methods: This was a cross-sectional study on pediatric TDTs aged 2-18 years old at Dr. Soetomo General Academic Hospital Surabaya, Indonesia conducted in 2020. They required blood transfusion every 2-4 weeks. We evaluated the ratio of upper/lower body segments, weight for age Z-score (WAZ), height for age Z-score (HAZ), and body mass index (BMI) Z-score, based on CDC growth chart as growth status parameters. Serum ferritin was checked every three months to determine iron overload and iron chelation (deferiprone, deferasirox and deferoxamine). We used Spearman correlation and Mann-Whitney U test to analyze between variables (α=0.05). Results: We enrolled 15/29 males with median age 10.5 years. Serum Ferritin had negative correlation with the ratio of upper/lower body segments (rho=-0.552; P=0.002), but not for HAZ (rho=-0.078; P=0.694), WAZ (rho=-0.186; P=0.342), BMI Z-score (rho=-0.089; P=0.653) especially if serum ferritin was above 2500 µ/L. In deferiprone group (n=8), the WAZ (P=0.034) and BMI Z-score (P=0.031) were lower; but the ratio of upper/lower body segments was greater (P=0.039) than the deferasirox group. Conclusion: Growth retardation was more visible in pediatric TDTs with high ferritin and in deferiprone group. The height and the ratio of upper/lower body segments of the body were more affected.